Upah, Jaminan Keselamatan Kerja, Bantuan Pemerintah: Potret Kesejahteraan Buruh Tani Perkebunan Tebu di Jatiroto - Andwitasari, Nindya Andwitasari; Yuliana Putri, Evayanti; Rifqi Nur Riansyah, Ahmad (CV. Publikasi Indonesia, 2022)
Welfare is one component that plays a major role for workers. The welfare in question is quite diverse, starting from wages, work safety guarantees, and government assistance. Wages are one of the crucial factors needed by workers to meet their daily needs. In addition, work safety guarantees are an important point to improve welfare in addition to wages. This study aims to find out more about the portrait of the welfare of sugarcane plantation workers in Jatiroto, related to wages, work safety guarantees, and government assistance. There are so many problems experienced by farm workers, especially after the COVID-19 Pandemic which has increasingly clouded the stability of the welfare of farm workers. The method of data collection carried out by researchers in this study were interviews and observations. The results of the interview show that Sugarcane Farmers in Jatiroto belong to a group of people whose lives are relatively within the poverty line. Of course because of how the Wage system, Work Safety Guarantee, and Government Assistance are not fulfilled for this group of workers. The wages received by farm laborers are minimal and sometimes not enough to meet their daily needs. Even the wages paid to workers often experience delays. In addition, the work safety guarantees that workers get are not completely evenly distributed due to the control of the foreman. This makes farm workers have to rely on government assistance so that this leads to a conclusion that the importance of sugar factories pay attention to discipline in paying wages to farm workers.